Science, engineering and technology in Britain. (Foreign and Commonwealth Office, 1997)
Science, engineering and technology affect our everyday lives in a multitude of ways. Their role is fundamental to the prosperity of a leading industrial and trading nation such as Britain, with the ability to compete successfully in today's highly competitive world markets depending increasingly on the production and bringing to market of innovative high-technology goods and services.